A self-supported Ni–Co perselenide nanorod array as a high-activity bifunctional electrode for a hydrogen-producing hydrazine fuel cell. Issue 36 (5th September 2018) - Wang, Genxiang; Chen, Junxiang; Cai, Pingwei; Jia, Jingchun; Wen, Zhenhai
Abstract : Simultaneous hydrogen production and electricity generation was achieved in a hybrid hydrazine fuel cell assisted by the electrochemical neutralization energy. Abstract : Although the fundamental processes of electrolytic hydrogen generation are relatively well understood, fundamental studies and explorations of the new concepts and materials for electrolysis are highly desirable to make renewable hydrogen sufficiently cost-competitive. Herein, we report a proof-of-concept for an alkaline–acid-based hydrogen generating hydrazine fuel cell by coupling the hydrazine oxidation reaction (HzOR) at the alkaline anode with the hydrogen evolution reaction (HER) at the acidic cathode. Furthermore, we verified that such a hybrid cell could simultaneously fulfill hydrogen production and electricity generation owing to harvesting of two types of electrochemical energies, i.e., electrochemical energy of the HzOR and the electrochemical neutralization energy. To this end, a bifunctional electrode comprising a three-dimensional nanoporous Ni–Co perselenide nanorod array (Ni x Co1− x Se) was designed and prepared by a facile two-step synthesis process, involving the initial in situ electroplating on a carbon cloth followed by subsequent selenization. The optimized electrode, i.e., Ni0.5 Co0.5 Se2, showed high electrocatalytic activity toward HzOR in alkaline electrolyte and HER in acidic medium. The optimized alkaline–acid hydrazine fuel cell, with the Ni0.5 Co0.5 Se2 electrode as both the cathode and anode, could potentially deliver a power density of 13.3 mW cm −2 at a current density of 54.7 mA cm −2 with good long-term stability and a faradaic efficiency of nearly 100% for hydrogen production.